2005
DOI: 10.1029/2004jc002621
|View full text |Cite
|
Sign up to set email alerts
|

A seasonal study of diatom dynamics in the North Atlantic during the POMME experiment (2001): Evidence for Si limitation of the spring bloom

Abstract: [1] The Si cycle in the northeast Atlantic (40°-43.5°N, 15°-21°W) was investigated in the winter, spring, and late summer during the Programme Océan Multidisciplinaire Méso Echelle (POMME) (2001). The aim of this study was to determine the principal causes of the onset and subsequent decline of the diatom bloom, with an emphasis on nutritional limitation processes. The siliceous compartment dynamics was characterized through silicic acid distribution, size-fractionated biogenic silica and Si uptake rates, Si u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 65 publications
(96 reference statements)
6
43
0
2
Order By: Relevance
“…Ward & Zafiriou 1988, Bianchi et al 1994, Ward 2005, but proved to be significant even during the spring bloom, which was followed by local phytoplankton blooms until May 2001 (Leblanc et al 2005). Nitrification was intense in the entire water column and was largely able to sustain plankton DIN demand.…”
Section: Nitrification and New Primary Productionmentioning
confidence: 98%
“…Ward & Zafiriou 1988, Bianchi et al 1994, Ward 2005, but proved to be significant even during the spring bloom, which was followed by local phytoplankton blooms until May 2001 (Leblanc et al 2005). Nitrification was intense in the entire water column and was largely able to sustain plankton DIN demand.…”
Section: Nitrification and New Primary Productionmentioning
confidence: 98%
“…Previous studies have used PDMPO as a proxy to quantify the amount of silica precipitated in whole communities and in isolated species (Leblanc et al 2005;Durkin et al 2012). In our study, a strong correlation was found between PDMPO fluorescence and silica content of cultured diatom species.…”
Section: Discussionmentioning
confidence: 99%
“…Deviations from transporter-like uptake have been observed in natural communities (Brzezinski and Nelson 1996;Leblanc et al 2005) and in laboratory isolates (Thamatrakoln and Hildebrand 2008;Finkel et al 2010), where uptake rates continue to increase linearly with increasing supply of silicic acid beyond the concentrations where maximum SITmediated uptake rates are typically reached. In these conditions, diatoms continue to incorporate silicic acid and increase silicification at high silicic acid concentrations (.…”
mentioning
confidence: 99%
“…At high latitude systems, the majority of picophytoplankton are eukaryotes and/or prokaryotic cyanobacteria belonging to the genus Synechococcus. The role of picophytoplankton in northern systems has received more attention in recent years van De Poll et al, 2016;Sherr et al, 2003;Tremblay et al, 2009), although traditionally the focus has been on larger, spring-blooming phytoplankton (Leblanc, 2005;Rees et al, 1999;Velasco et al, 2013). During bloom periods the relative abundance of picophytoplankton is low (Li et al 1993), but a bloom is a short-term feature and smaller phytoplankton and associated grazers dominate the rest of the year.…”
Section: Introductionmentioning
confidence: 99%